The Influence of Growing Media on the Growth of Kepok Tanjung Banana (Musa paradisiaca) During the Acclimatization Stage - Yulisa Fitri; Yosi Zendra Joni; Violita Violita (Jurnal Biologi Tropis, 2026)
Kepok Tanjung banana (Musa paradisiaca) is a superior variety with high economic value. Tissue culture is a promising propagation method, but the acclimatization stage is a critical bottleneck. The aim of this study was to test the effect of planting medium composition on the development of Kepok Tanjung banana seedlings during the acclimatization period. A completely randomized design was used with six planting medium treatments: soil (control), cocopeat, rice husk charcoal, soil + cocopeat (2:1), soil + rice husk charcoal (2:1), and soil + cocopeat + rice husk charcoal (2:1:1). Each treatment was repeated four times, with ten plantlets per replicate. Observations were made every two weeks for 12 weeks on parameters of survival, plant height, stem diameter, leaf dimensions, leaf count, root length, and fresh and dry weight. All growth parameters were found to be significantly influenced by the composition of the growing medium, according to data analysis conducted using ANOVA and Duncan's Multiple Range Test (DNMRT) at a 5% significance level. The mixture of soil and rice husk charcoal (2:1) provided the best results, with a survival rate of 95%, plant height of 19.94 cm, stem diameter of 9.95 mm, root length of 25.25 cm, and the highest fresh and dry weights (18.87 g and 1.96 g). This combination offered an optimal balance of aeration, moisture retention, and nutrient availability, supporting the plantlets' transition from in vitro to in vivo conditions. It is concluded that a mixture of soil and rice husk charcoal (2:1) is the most effective medium for the acclimatization of Kepok Tanjung banana plantlets.